Temporal changes in plasma and milk lipids in response to an esophageal bolus of rumen-protected fish oil in lactating Holstein dairy cows - J.E. Rico; V. Sáinz de la Maza-Escolà; N.D. Senevirathne; P. Deme; N.J. Haughey; R. Gervais; J.W. McFadden (Animal)
Feeding very-long-chain omega-3 (VLC n-3) fatty acids (FA), which are found in fish oil, may have beneficial effects on health, fertility, and milk production in the dairy cow. Rumen-protected technologies aim to prevent the ruminal biohydrogenation of VLC n-3 FA. To test the effects of these technologies on circulating FA and phospholipid concentrations, and milk FA concentrations, six mid-lactation, multiparous, pregnant Holstein dairy cows (mean ± SD: 155 ± 19 days in milk; 3.0 ± 0.5 body condition score; 3.2 ± 1.1 lactations; 644 ± 23 kg BW) were randomly assigned to treatments in a study with a replicated 3 × 3 Latin Square design. Cows were unsupplemented (control) or supplemented with a single esophageal bolus of a gelatin capsule containing a fish oil product coated in palm oil triglycerides or modified starch (TAG and STR, respectively). The provision of either fish oil product provided 10 g equivalent of VLC n-3 FA including 20:5 n-3 and 22:6 n-3. Cows were fed a total mixed ration to meet or exceed nutrient requirements and were milked thrice daily. Blood was sampled at 0, 2, 4, 6, 8, 10, 12, 16, 18, 20, 24, and 36 h, relative to bolus administration. A 7-d washout period was utilized between each bolus delivery. Extracted plasma was analyzed for individual FA and phospholipid concentrations using gas chromatography and mass spectrometry. Separated milk fat was analyzed for individual milk FA using gas–liquid chromatography and a flame-ionization detector. Data were analyzed under a mixed model with the random effect of cow, and the fixed effects of treatment, hour, and period. Plasma concentrations of 20:5 n-3 and 22:6 n-3 increased over time by TAG and STR, relative to control. Plasma concentrations of lysophophatidylcholine-20:5, −22:5 and −22:6, and phosphatidylcholine (PC)-38:5 and −38:6 were higher in TAG and STR by h 10, relative to control. Plasma PC-40:5 and −40:6 concentrations were greater in cows administered STR by h 10, relative to TAG. Total milk n-3 increased over time in treated cows compared to control. We conclude that triglyceride- or starch-encapsulated fish oil increases the plasma and milk concentrations of VLC n-3 FA and phospholipids containing these acyl chains in lactating cows.